CIRCULATING BIOMARKERS OF SYSTEMIC INFLAMMATORY RESPONSE IN THE ASSESSMENT OF POSTPERICARDIOTOMY SYNDROME IN PATIENTS AFTER CARDIAC SURGERY - A. M. Gusakova; T. E. Suslova; M. L. Diakova; B. N. Kozlov (Медицинская иммунология)
Postpericardiotomy syndrome (PCTS) is one of the most frequent cardiac surgery complications seen in 9-65% of patients. Despite its widespread occurrence, the mechanisms of the development of PCTS are still understudied. drug. The use of colchicine in cardiac surgery patients is of particular interest. Due to the ability of this drug the colchicine mechanisms of action are able to inhibit the mobilization of the NLRP3 inflammasome assembly, to suppress the activation of caspase-1. As a result, it can prevent the release of proinflammatory cytokines, namely IL-1β and IL-18. There are conflicting data on the effect of colchicine on the PCTS progression within the systemic inflammatory response after cardiac surgery. In this regard, it was important to study the dynamics of serum levels of IL-6, IL-10, IL-1β, and TNFα in patients before coronary artery bypass grafting (T1), 6 hours (T2), and 10 days (T3) after surgery, and to evaluate the effect of colchicine on the development of PCTS. The results of our research showed a significant increase of IL-10 in both groups 6 hours after surgery. However, on the 10th day, the increase in the level of IL-10, compared with the initial values, was higher in the 1st group – 2 times, compared with the 2nd group. In both groups, showed significant increase in serum concentration of IL-6 after 6 h surgery, with a subsequent decrease in the expression at the stage of T3, while the IL-6 levels in the 2nd group was statistically notably higher than T1. The incidence of pleurisy was lower in the group of patients taking colchicine. Only in the 1st group IL-6 levels were directly associated with IL-10. In patients with pleurisy, the level of released IL-10 and TNFα was significantly higher in the 2nd group. There were no significant intergroup differences in serum levels of IL-1β and TNFα, as well as significant changes in IL-1β between the stages of observation. Analysis of TNFα expression revealed significant differences in TNFα content in the 1st group between the T1-T3 and T2-T3 stages. In both groups, multiple positive associations were found between the studied indicators. Thus, data were obtained indicating the antiinflammatory effect of colchicine in cardiac surgery patients. This was clinically expressed in a tendency to a lower incidence of pleurisy, and was accompanied by increased expression of IL-10, which has an antiinflammatory and immunomodulatory effect against the background of the drug in the postoperative period.